2016
DOI: 10.1093/annonc/mdw011
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of baseline total metabolic tumor volume (TMTV0) measured on FDG-PET/CT in patients with peripheral T-cell lymphoma (PTCL)

Abstract: TMTV0 appears as an independent predictor of PTCL outcome. Combined with PIT, it could identify different risk categories at diagnosis and warrants further validation as a prognostic marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
86
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 26 publications
8
86
0
2
Order By: Relevance
“…The agreement between the dichotomization of patients in low-and high-TMTV groups obtained with the 41% SUV max method and each adaptive method was tested with the Cohen k-coefficient. Survival functions were also calculated for each method using the threshold of 230 cm 3 determined with the 41% SUV max method for PFS and OS (5).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The agreement between the dichotomization of patients in low-and high-TMTV groups obtained with the 41% SUV max method and each adaptive method was tested with the Cohen k-coefficient. Survival functions were also calculated for each method using the threshold of 230 cm 3 determined with the 41% SUV max method for PFS and OS (5).…”
Section: Discussionmentioning
confidence: 99%
“…The principle of these adaptive methods developed for radiotherapy planning of solid tumors is to adapt the threshold following a fitting model according to 1 or 2 characteristic image parameters, such as the SUV or the contrast. In a previous study, we have demonstrated in a retrospective group of PTCL patients that TMTV measured with the 41% SUV max threshold method was a good predictor of outcome (5). The aim of the present study was to compare in the same series, taken as a model of diffuse lymphoma, different adaptive thresholding methods with this fixed 41% method and to evaluate whether these adaptive thresholding methods were better predictors of outcome than a fixed relative threshold.…”
mentioning
confidence: 89%
See 3 more Smart Citations